ONLINE TEACHING OF GRAPHIC COURSES IN THE PANDEMIC - Alina Angelica ANGHEL; Vanda Ligia DANAILA (Journal of Industrial Design and Engineering Graphics, 2023)
The paper highlights certain aspects regarding the online teaching of graphic courses for the students of the 1st year of the Faculty of Machine Manufacturing and Industrial Management, during the COVID 19 pandemic. One can see the premises and the statistically processed results of certain tests of technical drawing with physical and online teaching for the students of the above mentioned faculty, their perceptions and opinions regarding online and hybrid education. The conclusions refer to the improvement of online teaching methods for graphic courses and to the role of Pedagogy which cannot be replaced by the technological evolution.